Research on 10 kV Cable Insulation Detection Method Based on Ground Current Phase Variation - Gang Liu; Yuanming Zhang; Tonghui Ye; Dongdong Zhang; Peigen Cao; Yulan Che (Energies)
In view of the limitations of traditional offline detection and external excitation online detection of 10 kV cables, this paper proposes a method to evaluate the insulation aging condition of power cables by online measuring of the phase angle of the cable’s ground current, and explores the impact of load fluctuations on cable insulation. By setting the relative permittivity of the cable to characterize the phase variation of the ground current under different aging degrees, and analyzing the phase variation of the cable’s ground current under different load changes at the same aging degree, a load correction-based dynamic dielectric loss evaluation method for cables is proposed. Through the construction of cable simulation models and the processing of field data, the following conclusions have been reached: Under a 1 MW load, the phase angle of the sheath grounding current in the aged phase increases as the dielectric constant of the insulation increases. At the same aging degree, with an increase in load, the phase differences of the aging phase sheath ground current and the steel armor ground current both show a decreasing trend. To eliminate the impact of load, a dynamic dielectric loss load correction method is proposed, and combined with field data analysis, the dynamic dielectric loss of cables under different loads is corrected to a 1 MW load. Specifically: Under 0.3 MW, the correction coefficients k for the sheath and steel armor are 0.609 and 0.778, respectively. Under 3.5 MW, the correction coefficients k for the sheath and steel armor are 1.435 and 1.089, respectively. This study provides a theoretical basis and experimental verification for online cable monitoring methods.